Anxiety in Children Preschool: Can it be overcome with gradual exposure? - Rosyada, Amelinda Regita Nurfelita; Karmiyati, Diah (Universitas Muhammadiyah Malang, 2024)
Anxiety problems do not only occur in adolescence or adulthood. Children also often experience anxiety. Anxiety that occurs in childhood often occurs when they are in the school environment. Symptoms that occur in this anxiety include physical characteristics, behavioral characteristics and cognitive characteristics. Anxiety in children when at school is characterized by not being able to go to school independently, so parents must always wait for them. The purpose of this study was to determine the effectiveness of behavioral therapy in reducing anxiety in preschool children at school. The assessment methods used were clinical interviews and observations. The technique in behavioral therapy used was gradual exposure, where the subject will be faced with situations that trigger feelings of anxiety gradually. The results of the study showed that there was a decrease in the level of anxiety, which was also marked by the subject being able to go to school independently. Masalah kecemasan tidak hanya terjadi pada masa remaja atau dewasa. Anak-anak juga sering mengalami kecemasan. Kecemasan yang terjadi pada masa kanak-kanak sering terjadi ketika mereka berada di lingkungan sekolah. Gejala yang terjadi pada kecemasan ini meliputi karakteristik fisik, karakteristik perilaku dan karakteristik kognitif. Kecemasan pada anak ketika di sekolah ditandai dengan tidak dapat pergi ke sekolah secara mandiri, sehingga orang tua harus selalu menunggu mereka. Tujuan dari penelitian ini adalah untuk mengetahui efektivitas terapi perilaku dalam menurunkan kecemasan pada anak prasekolah di sekolah. Metode penilaian yang digunakan adalah wawancara klinis dan observasi. Teknik dalam terapi perilaku yang digunakan adalah paparan bertahap, dimana subjek akan dihadapkan pada situasi yang memicu perasaan cemas secara bertahap. Hasil penelitian menunjukkan bahwa terjadi penurunan tingkat kecemasan, yang juga ditandai dengan subjek mampu pergi ke sekolah secara mandiri.